THE MAKING OF DART BOARD GAME FOR ELEMENTARY SCHOOL STUDENTS - Uci Puspasasri; A. Malik (Politeknik Negeri Bengkalis, 2017)
Abstract:The mastery of vocabulary is one of important factors to support language skill. Meanwhile, to make the student master the vocabulary is not an easy thing. They need media to help them in learning process. There are some ways should be applied to help student understand easily. One of them is learning vocabulary by using game.The main purpose of this research is to make a Dart Board game. This game can be used as an alternative learning vocabulary especially for Elementary School Students. The result of this study is a set of Dart Board Game, four set sheets of cards, and six darts. This game can be used in classes during learning-teaching process to help the students memorizeEnglish vocabulary easly.Â Keywords: Dart Board Game, Vocabulary